Detection and Profiling of AntibioticResistance among Culturable Bacterial Isolates in Vended Food and Soil Samples - Muriuki, Susan W.; Neondo, Johnstone O.; Budambula, Nancy (Hindawi, 2020)
+e emergence and persistence of antibiotic resistance remain formidable health challenges. +is study aimed at detecting and profiling antibiotic resistance of bacterial contaminants in vended food and the environment. Seventy antibiotic-resistant bacterial isolates were isolated from fried fish, African sausages, roasted meat, smokies, samosa, chips (potato fries), vegetable salads, and soil samples collected from Embu Town and Kangaru Market in Embu County, Kenya. +e antibiotic susceptibility test, morphological and biochemical characterization, antibiosis assay, polymerase chain reaction-based detection of antibiotic resistance genes, and sequencing of the 16S rRNA gene were done. Analysis of variance on all measured data was done, and Tukey’s honest test was used to compare and separate mean diameters of zones inhibition. Resistance of bacterial isolates to antibiotics was chloramphenicol (90%), cefotaxime (84.29%), nalidixic acid (81.43%), tetracycline (77.14%), amoxicillin (72.86%), gentamycin (48.57%), streptomycin (32.86%), and trimethoprim + sulphamethoxazole (30%). Isolate KMP337, Salmonella spp., exhibited highly significant antibiosis against S. aureus recording a mean inhibition diameter and standard error (SE) of 16.33 ± 0.88 mm, respectively, at P 0.001. +e 70 bacterial isolates belonged to Bacillus, Paraclostridium, Lysinibacillus, Virgibacillus, and Serratia genera. +e study isolated Bacillus wiedmannii (KC75) which is a risk group 2 as well as Serratia marcescens (KMP95) and Bacillus anthracis (KS606) which are risk group 3 organisms. +e presence of antibiotic resistance genes Tet A, BlaTEM, StrB, Dfr A, Amp, and FloR genes was confirmed by a polymerase chain reaction. Samples from Kangaru Market recorded a higher (88.57%) proportion of resistant isolates as compared to isolates from Embu Town (11.43%). +e study confirmed the presence of antibioticresistant bacteria in vended fast food and the soil in Embu Town and Kangaru Market. +is study calls for continuous monitoring of bacterial status and hygienic handling of vended food.